Enhancing Passenger Navigation: A Visibility Index Analysis of Wayfinding Quality in SHIAM Airport Terminal - Agrie Pratama Harwinanto; Pribadi Widodo; Deddy Wahjudi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DRPM), ITS, 2025)
Complex airport environments pose significant wayfinding challenges for passengers, particularly within large international hubs like Sultan Hasanuddin International Airport (SHIAM) in Makassar, Indonesia. This study examines the quality of wayfinding at SHIAM, aiming to identify areas for improvement and inform future design decisions. Employing a quantitative approach, the study combines objective spatial data from a visibility index (VI) analysis of 23 key terminal facilities with subjective wayfindingexperiences gleaned from existing case studies. The VI analysis assessed visual access, layout complexity, and facility importance, revealing an overall VI score: 0,599, indicating moderate wayfinding difficulties. These findings highlight the need for targeted interventions to address visibility and accessibility issues, particularly in critical facilities. By optimizing wayfinding within the terminal, the airport can enhance passenger experience and operational efficiency.